By Choice or by Force? Exploring the Nature of Informal Employment in Urban Mexico - Robert Duval Hernández (Institute of Labor Economics (IZA), 2021)
Using a special module of the 2015 Mexican Labour Force Survey with information on workers' preferences for jobs with social security coverage, I estimate that 80 per cent of informal workers in large urban areas would prefer to work in a job that provides them with such coverage. The estimation of a discrete choice econometric model which distinguishes between wanting a formal job and the probability of getting one shows that schooling increases the chances of being hired in formal employment and of having higher earnings in it. Women with greater responsibilities at home are less likely to want formal employment, and they also face a lower probability of being hired in such jobs. The findings indicate the segmentation of Mexican labour markets and the rationing of formal jobs, together with the existence of workers who voluntarily participate in informal employment. However, the estimated fraction of involuntary informal workers is quite high.
Keywords: O17; 330; informal employment; labour markets; segmentation; rationing